2017
DOI: 10.5937/jpea1704197o
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of edible coating on minimally processed pomegranate fruits

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Change in aril colour was not clear; however, application of MC + TO 0.5% and MC + TO 0.25% coatings inhibits the loss of redness compared to uncoated fruit arils. Likewise, Öz and Eker [42] reported reduced loss of redness in arils extracted from "Tarom" pomegranates treated with starch coatings enriched with of N. sativa before cold storage (4 • C and 95% RH) for 12 days. The observed changes in chroma values corroborate with Azarakhsh et al [43] who observed a decrease over time in chroma values of fresh-cut pineapple coated with gellan gum-based coating during cold storage.…”
Section: Colourmentioning
confidence: 92%
“…Change in aril colour was not clear; however, application of MC + TO 0.5% and MC + TO 0.25% coatings inhibits the loss of redness compared to uncoated fruit arils. Likewise, Öz and Eker [42] reported reduced loss of redness in arils extracted from "Tarom" pomegranates treated with starch coatings enriched with of N. sativa before cold storage (4 • C and 95% RH) for 12 days. The observed changes in chroma values corroborate with Azarakhsh et al [43] who observed a decrease over time in chroma values of fresh-cut pineapple coated with gellan gum-based coating during cold storage.…”
Section: Colourmentioning
confidence: 92%
“…Considering this, developing postharvest treatments for preserving "Wonderful" pomegranate is a high priority. Several authors have reported edible coatings as a promising treatment for pomegranate whole fruit and fractions to minimize postharvest losses during storage and shelf life [23,36,[49][50][51]. However, limited studies derive edible coating formulations with optimum concentrations of ingredients to potentially extend pomegranate storage and shelf-life.…”
Section: Introductionmentioning
confidence: 99%